RESPON PERTUMBUHAN VEGETATIF TANAMAN PISANG BARANGAN (Musa paradisiaca sapientum L.) AKIBAT PENGGUNAAN PUPUK KOTORAN KAMBING DAN JAMUR Trichoderma harzianum - Muhammad Yusuf Dibisono (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2014)
This study aims to get the response of plant vegetative growth banana (Musa paradisiaca sapientum L) effect to the use of goat manure and fungus Trichoderma harzianum and the combination of both treatments. The research was conducted in the area of the garden village Selamat District of Biru-Biru with altitude 200 m above sea level. The study was conducted from April 2014 through August 2014. This study used a randomized block design factorial consisting of two factors, namely goat manure dose factor (K) consists of 3 levels of treatment: K0 = 0 kg/plant, K1 = 2.5 kg/plant, K2 = 5 kg/plant and dosing frequency factor fungus Trichoderma harzianum (T) consists of 3 levels of treatment are: T0 = 0 g/plant, T1 = 25 g/plant and T2 = 50 g/plant. Parameters were observed in this study is plant height (cm), number of leaves (pieces), stem diameter (cm). The results showed goat manure significantly affected plant height and diameter growth of banana stem. Goat manure is best obtained at a dose of 5 kg/plant. Fungus Trichoderma harzianum significant effect on plant height at a dose of 50 g/plant, but no real effect on the number of leaves and stem diameter. Interaction dose goat manure and fungus Trichoderma harzianum giving no real effect on the vegetative growth of banana.